Structural disassembly-free thermal insulation formwork material based on fiber reinforced concrete and preparation method of structural disassembly-free thermal insulation formwork material

By combining fiber-reinforced concrete materials, structural non-removable thermal insulation formwork is prepared, which solves the problems of low turnover rate of traditional formwork materials and poor interfacial adhesion of thermal insulation systems, and achieves efficient, low-cost construction and green energy-saving effects.

CN120965219APending Publication Date: 2025-11-18CCCC THIRD HARBOR ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511077196.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing wooden and aluminum alloy formwork have problems such as low turnover rate, complex construction and high cost in concrete pouring. Traditional insulation systems increase the construction cycle and cost, and have problems such as poor interface adhesion, thermal bridging effect and insufficient fire resistance.

Method used

A structurally removable thermal insulation template material is prepared by using fiber-reinforced concrete material combined with cement, fly ash, mineral powder, silica fume, quartz sand, vacuum glass microspheres, and other components. After being mixed evenly, the template is formed in a mold and cured to form a template with good thermal insulation and mechanical properties.

Benefits of technology

It achieves customized applicability of multifunctional templates, simplifies construction processes, reduces costs, improves building energy efficiency, reduces waste, conforms to the concept of green building, and improves construction efficiency and building quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120965219A_ABST
    Figure CN120965219A_ABST
Patent Text Reader

Abstract

The invention discloses a structural non-dismantling thermal insulation formwork material based on fiber reinforced concrete. The environment-friendly building material is prepared from the following components: 10.0% to 12.0% of cement, 2.0% to 4.0% of fly ash, 3.0% to 5.0% of S95-grade mineral powder, 1.5% to 2.5% of SF92-grade silica fume, 17.0% to 21.0% of quartz sand, 2.0% to 4.0% of fine vacuum glass beads, 28.0% to 32.0% of coarse vacuum glass beads, 0.5% to 0.7% of polypropylene fibers, 0.3% to 0.5% of plant fibers, 0.3% to 0.5% of cellulose ether, 0.3% to 0.5% of latex powder, 0.1% to 0.3% of a coupling agent and 22.0% to 24.0% of water. The invention further discloses a preparation method of the structural non-dismantling heat preservation formwork material based on the fiber reinforced concrete. The overall energy efficiency and construction efficiency of the cast-in-place concrete structure can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a structural, non-removable thermal insulation formwork material based on fiber-reinforced concrete and its preparation method. Background Technology

[0002] Currently, the construction industry uses wooden or aluminum alloy formwork as molding materials for concrete pouring. However, wooden formwork has a low turnover rate, requires installation and dismantling during construction, and involves complex procedures and high labor costs. Aluminum alloy formwork, due to the independent design of each project, requires optimization based on the project structure before processing, resulting in poor versatility across multiple projects and high per-project costs. Meanwhile, national requirements for green and energy-efficient buildings and prefabricated building construction are increasingly stringent. Traditionally, an external or internal insulation system is designed after the main concrete structure is completed. The internal insulation design and construction sequence is: leveling layer, insulating mortar layer, wire mesh, plaster layer, putty layer, and decorative layer; external insulation generally uses dry-hanging insulation panels. This approach not only increases construction time and costs but also easily leads to thermal bridging, affecting the overall energy efficiency of the building. To address these issues, some non-removable insulation formwork products have emerged on the market, such as wire mesh composite insulation panels and sandwich insulation panels. However, these products generally suffer from poor interfacial adhesion, significant thermal bridging, and insufficient fire resistance.

[0003] In recent years, researchers have begun to explore the use of new materials and technologies to improve these problems. For example, some studies have focused on using high-performance fiber-reinforced concrete (FRC) to improve the mechanical properties and durability of formwork.

[0004] Glass microspheres, as a lightweight and efficient thermal insulation material, are widely used in building materials. However, how to organically combine these materials to form a multifunctional, non-removable formwork system that integrates structural support, thermal insulation, and fire resistance remains an urgent problem to be solved. To improve building assembly rates, reduce costs and increase efficiency, and meet the green and energy-saving requirements of building construction, it is imperative to develop a structural non-removable thermal insulation formwork material based on fiber-reinforced concrete and its preparation method. Summary of the Invention

[0005] To address the aforementioned problems in the existing technology, this invention provides a structural non-removable thermal insulation formwork material based on fiber-reinforced concrete and its preparation method, which can effectively improve the overall energy efficiency and construction efficiency of cast-in-place concrete structures.

[0006] The technical solution to achieve the above objectives is:

[0007] One of the present inventions discloses a fiber-reinforced concrete-based structural insulation formwork material that requires no removal, which is composed of the following components by volume percentage:

[0008] Cement 10.0%-12.0%, fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, quartz sand 17.0%-21.0%, fine vacuum glass microspheres 2.0%-4.0%, coarse vacuum glass microspheres 28.0%-32.0%, polypropylene fiber 0.5%-0.7%, plant fiber 0.3%-0.5%, cellulose ether 0.3%-0.5%, latex powder 0.3%-0.5%, coupling agent 0.1%-0.3%, water 22.0%-24.0%.

[0009] Preferably, by volume percentage, it is composed of the following components:

[0010] Cement 11.0%, fly ash 3.0%, S95 grade mineral powder 4.0%, SF92 grade silica fume 2.0%, quartz sand 19.0%, fine vacuum glass microspheres 3.0%, coarse vacuum glass microspheres 30.0%, polypropylene fiber 0.6%, plant fiber 0.4%, cellulose ether 0.4%, latex powder 0.4%, coupling agent 0.2%, water 23.0%.

[0011] Preferably, the quartz sand particles are 0.15-0.6 mm in size, the fine vacuum glass microspheres are 120 μm in size, and the coarse vacuum glass microspheres are 2.5-3.5 mm in size.

[0012] Preferably, fine vacuum glass microspheres and coarse vacuum glass microspheres are replaced with aerogel or expanded perlite.

[0013] Preferably, the cement is 42.5 grade silicate cement, the polypropylene fiber is 12mm monofilament fiber, the plant fiber is 5mm natural fiber, and the coupling agent is silane.

[0014] A method for preparing a non-removable thermal insulation formwork material based on fiber-reinforced concrete, as described in the second part of this invention, includes:

[0015] Step S1: Prepare the required cement, fly ash, mineral powder, silica fume, fine vacuum glass microspheres, coarse vacuum glass microspheres, polypropylene fiber, plant fiber, cellulose ether, coupling agent, latex powder, and water.

[0016] Step S2: Cement, fine vacuum glass microspheres, coarse vacuum glass microspheres, polypropylene fiber and plant fiber are mixed evenly according to the designed ratio to obtain the mixed dry material.

[0017] Step S3: Add cellulose ether, coupling agent and latex powder to the dry mixture and continue to stir until homogeneous;

[0018] Step S4: Add an appropriate amount of water gradually according to the specific situation, mix evenly, and obtain the mixed mortar;

[0019] Step S5: Pour the mortar into the mold, compact and level the surface, cure for 20-48 hours under standard conditions, then demold and continue curing under natural conditions for 5-7 days.

[0020] Preferably, in step S1, the raw materials consist of the following components by volume percentage:

[0021] Cement 10.0%-12.0%, fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, quartz sand 17.0%-21.0%, fine vacuum glass microspheres 2.0%-4.0%, coarse vacuum glass microspheres 28.0%-32.0%, polypropylene fiber 0.5%-0.7%, plant fiber 0.3%-0.5%, cellulose ether 0.3%-0.5%, latex powder 0.3%-0.5%, coupling agent 0.1%-0.3%, water 22.0%-24.0%.

[0022] Preferably, in step S5, the standard conditions are: temperature 45-50℃.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] The template material of this invention can be customized according to different architectural design requirements, and is suitable for various complex shapes and special structures, such as irregular columns, beams, shear walls, etc., to meet diverse construction needs;

[0025] The formulation and molding process of the material of this invention is simple and easy to implement, requiring no complex equipment or highly skilled workers, which facilitates large-scale production and on-site construction.

[0026] This invention reduces environmental impact by minimizing waste generated during template removal; simultaneously, the material has excellent thermal insulation properties, which helps reduce building energy consumption and achieve energy conservation and emission reduction goals.

[0027] This invention does not require removal after concrete pouring and can be used directly as a permanent insulation layer, simplifying the construction process, reducing the time for formwork removal and subsequent insulation layer construction, and significantly improving construction efficiency.

[0028] Some raw materials, such as glass microspheres, can be made from recycled glass, which promotes the recycling of resources and is in line with the concept of green building.

[0029] This invention reduces the construction steps of formwork removal and subsequent mortar plastering, thereby reducing labor and material costs and lowering overall costs. In addition, the durability and stability of the formwork material also reduce the cost of later maintenance and replacement. It helps to improve the overall quality and safety of buildings, improve the living environment, and enhance the quality of life for residents. Attached Figure Description

[0030] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:

[0031] Figure 1 This is a flowchart of the preparation method of the structural non-removable thermal insulation formwork material based on fiber-reinforced concrete according to the present invention;

[0032] Figure 2 This is a schematic diagram of the thermal insulation template material obtained after mixing, compacting, leveling, and curing in this invention;

[0033] Figure 3 This is a schematic diagram of the internal structure of the thermal insulation template material in this invention. Detailed Implementation

[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] The structural non-removable thermal insulation formwork material based on fiber-reinforced concrete is composed of the following components by volume percentage:

[0036] The composition of the components is as follows: cement 10.0%-12.0%, fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, quartz sand 17.0%-21.0%, fine vacuum glass microspheres 2.0%-4.0%, coarse vacuum glass microspheres 28.0%-32.0%, polypropylene fiber 0.5%-0.7%, plant fiber 0.3%-0.5%, cellulose ether 0.3%-0.5%, latex powder 0.3%-0.5%, coupling agent 0.1%-0.3%, and water 22.0%-24.0%, as detailed in Table 1.

[0037]

[0038] Table 1

[0039] In this embodiment, the product is specifically composed of the following components by volume percentage:

[0040] The composition is as follows: cement 11.0%, fly ash 3.0%, S95 grade mineral powder 4.0%, SF92 grade silica fume 2.0%, quartz sand 19.0%, fine vacuum glass microspheres 3.0%, coarse vacuum glass microspheres 30.0%, polypropylene fiber 0.6%, plant fiber 0.4%, cellulose ether 0.4%, latex powder 0.4%, coupling agent 0.2%, and water 23.0%. The proportions of these components are adjusted according to the construction environment and are not fixed.

[0041] In the embodiments, the size of the quartz sand particles is 0.15-0.6 mm, the size of the fine vacuum glass microspheres is 120 μm, and the size of the coarse vacuum glass microspheres is 2.5-3.5 mm.

[0042] In this embodiment, the cement is grade 42.5 silicate cement with a 28-day compressive strength ≥ 42.5 MPa, a 28-day flexural strength ≥ 6.5 MPa, and a specific surface area of ​​340-370 m². 2 / kg; Polypropylene fiber is a 12mm monofilament fiber with a density of 0.91kg / m³. 3 The mortar has a tensile strength ≥300MPa and a diameter of 10-40μm; the plant fiber is a 5mm natural fiber with a diameter of 10-250μm, an elongation at break of 10-30%, and a tensile strength ≥2000MPa; the cellulose ether has a density ≥370g / L, which improves the mortar's water retention capacity, fluidity, and workability, as well as its initial strength and prevents cracking; the latex powder has a density of 1.2-2.0g / m³. 3 This improves the compressive and flexural strength of the mortar, increases its thixotropy and anti-sag properties, enhances cohesion, prolongs open time, and strengthens water retention; the coupling agent is a silane with a density of 0.942-0.951 g / m³. 3 With a pH value of 9.0-10.0, it can improve bonding strength, water resistance and weather resistance.

[0043] In another embodiment, different types of fibers (such as carbon fiber, basalt fiber, etc.) can be selected according to specific needs, and the fiber length and diameter can be adjusted. For example, the fiber length can be increased to 15mm-20mm to further improve the toughness and crack resistance of the material.

[0044] In another embodiment, suitable thermal insulation materials are used to replace fiber cement-based aggregates to achieve both thermal insulation and structural performance. Fiber cement-based aggregates refer to fine and coarse vacuum glass microspheres. Suitable thermal insulation materials include aerogels, expanded perlite, and polystyrene boards.

[0045] In another embodiment, the fine vacuum glass microspheres and coarse vacuum glass microspheres are replaced with aerogel or expanded perlite.

[0046] In another embodiment, functional additives, such as waterproofing agents and flame retardants, can be added to the mixed dry materials to enhance the waterproof and fire-resistant properties of the material, as well as different types of coupling agents; the fiber length will be dynamically adjusted according to the raw materials and construction environment, and is not a fixed length. For example, adding an appropriate amount of silicone waterproofing agent can give the material a better waterproof effect.

[0047] like Figure 1 As shown, a method for preparing a non-removable thermal insulation formwork material based on fiber-reinforced concrete includes:

[0048] Step S1: Prepare the required cement, fly ash, mineral powder, silica powder, fine vacuum glass microspheres, coarse vacuum glass microspheres, polypropylene fiber, plant fiber, cellulose ether, coupling agent, latex powder, and water.

[0049] In this embodiment, the raw materials consist of the following components by volume percentage:

[0050] The composition of the mixture is as follows: Cement 10.0%-12.0%, Fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, Quartz sand 17.0%-21.0%, Fine vacuum glass microspheres 2.0%-4.0%, Coarse vacuum glass microspheres 28.0%-32.0%, Polypropylene fiber 0.5%-0.7%, Plant fiber 0.3%-0.5%, Cellulose ether 0.3%-0.5%, Latex powder 0.3%-0.5%, Coupling agent 0.1%-0.3%, Water 22.0%-24.0%. In step S2, the cement, fine vacuum glass microspheres, coarse vacuum glass microspheres, polypropylene fiber, and plant fiber are mixed evenly according to the designed proportions to obtain the mixed dry material.

[0051] Step S3: Add cellulose ether, coupling agent and latex powder to the dry mixture and continue to stir until homogeneous.

[0052] Step S4: Add an appropriate amount of water gradually according to the specific situation, mix evenly, and obtain the mixed mortar.

[0053] Step S5: Pour the mortar into the mold, compact and level the surface, and cure it under standard conditions (temperature 45-50℃) for 20-48 hours. Then demold and continue curing under natural conditions for 5-7 days to obtain the thermal insulation formwork material. Figure 2 , 3 As shown.

[0054] In the embodiments, the curing conditions can be optimized according to the actual situation, such as extending the curing time or increasing the curing temperature, in order to further improve the mechanical properties and durability of the material.

[0055] In the embodiments, different molding processes, such as vibration molding and pressure molding, can be adopted as needed during actual production to improve the density and uniformity of the material.

[0056] The final thermal insulation template material will undergo the following material performance tests:

[0057] Compressive strength: The compressive strength is guaranteed to be no less than 60 MPa through standard specimen testing.

[0058] Flexural strength: The flexural strength is guaranteed to be no less than 10 MPa through standard specimen testing.

[0059] Thermal insulation performance: Thermal conductivity testing ensures that the material has good thermal insulation properties.

[0060] Fire resistance: The materials meet the Class A fire resistance standard by passing fire rating tests.

[0061] The template material obtained by this invention does not need to be removed after the concrete is poured. It also has good mechanical properties (such as compressive strength of not less than 60 MPa and flexural strength of not less than 10 MPa), thermal insulation properties, fire resistance properties and construction adaptability, which can effectively improve the overall energy efficiency and construction efficiency of cast-in-place concrete structures.

[0062] According to the experiment, the thermal insulation template material can effectively improve the strength of the specimen and increase the flexural-compression ratio, which greatly improves its mechanical properties and toughness. On the other hand, it significantly reduces its shrinkage rate and slows down the shrinkage rate. The structural non-removable thermal insulation template material based on fiber reinforced concrete provided by this invention can reach the shrinkage plateau in 5-7 days, which greatly improves its early crack resistance.

[0063] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A structure demountable thermal insulation formwork material based on fiber reinforced concrete, characterized by, consists of, by volume percentage: cement 10.0%-12.0%, fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, quartz sand 17.0%-21.0%, fine vacuum glass microbeads 2.0%-4.0%, coarse vacuum glass microbeads 28.0%-32.0%, polypropylene fiber 0.5%-0.7%, plant fiber 0.3%-0.5%, cellulose ether 0.3%-0.5%, latex powder 0.3%-0.5%, coupling agent 0.1%-0.3%, water 22.0%-24.0%.

2. The fiber reinforced concrete based structural stay-in-place thermal form material according to claim 1, characterized in that, consists of, by volume percentage: cement 10.0%-12.0%, fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, quartz sand 17.0%-21.0%, fine vacuum glass microbeads 2.0%-4.0%, coarse vacuum glass microbeads 28.0%-32.0%, polypropylene fiber 0.5%-0.7%, plant fiber 0.3%-0.5%, cellulose ether 0.3%-0.5%, latex powder 0.3%-0.5%, coupling agent 0.1%-0.3%, water 22.0%-24.0%.

3. The fiber reinforced concrete based structural stay-in-place thermal form material according to claim 1, wherein, The particle size of the quartz sand is 0.15-0.6mm, the particle size of the fine vacuum glass microbeads is 120μm, and the particle size of the coarse vacuum glass microbeads is 2.5-3.5mm.

4. The fiber reinforced concrete based structural stay-in-place thermal form material of claim 1, wherein, The fine vacuum glass microbeads and the coarse vacuum glass microbeads are replaced by aerogel or expanded perlite.

5. The fiber reinforced concrete based structural stay-in-place thermal form material of claim 1, wherein, The cement is 42.5 grade Portland cement, the polypropylene fiber is 12mm monofilament fiber, the plant fiber is 5mm natural fiber, and the coupling agent is silane type.

6. A method of manufacturing a demountable thermal insulation formwork material based on fiber reinforced concrete according to claim 1, characterized in that, It comprises: Step S1, preparing the required cement, fly ash, mineral powder, silica powder, fine vacuum glass microbeads, coarse vacuum glass microbeads, polypropylene fiber, plant fiber, cellulose ether, coupling agent, latex powder and water; Step S2, mixing the cement, fine vacuum glass microbeads, coarse vacuum glass microbeads, polypropylene fiber and plant fiber according to the designed proportion to obtain the mixed dry material; Step S3, adding cellulose ether, coupling agent and latex powder in the dry mixed material and continuing to stir uniformly; Step S4, adding appropriate amount of water according to the specific situation and mixing uniformly to obtain the mixed mortar; Step S5, pouring the mortar into the mold, compacting and leveling the surface, curing for 20-48 hours under standard conditions, then demolding, and continuing to cure for 5-7 days under natural conditions.

7. The preparation method according to claim 6, characterized in that, In the step S1, the raw materials consist of, by volume percentage: cement 10.0%-12.0%, fly ash 2.0%-4.0%, S95 grade mineral powder 3.0%-5.0%, SF92 grade silica fume 1.5%-2.5%, quartz sand 17.0%-21.0%, fine vacuum glass microbeads 2.0%-4.0%, coarse vacuum glass microbeads 28.0%-32.0%, polypropylene fiber 0.5%-0.7%, plant fiber 0.3%-0.5%, cellulose ether 0.3%-0.5%, latex powder 0.3%-0.5%, coupling agent 0.1%-0.3%, water 22.0%-24.0%.

8. The preparation method according to claim 6, characterized in that, In the step S5, the standard conditions are: temperature 45-50℃.